أي تكيف لشركات التأمين الجزائرية مع القواعد التوجيهية للملاءة2 ؟any Adaptation Of Algerian Insurance Companies With The Solvency Guidelines 2? - مرقوم, كلثوم; حدوش, شروق (جامعة الوادي - University of Eloued, 2022)
ملخص: نهدف من خلال هذه الدراسة الى بحث الية تطبيق الدعائم الثلاثة للملاءة 02 على قطاع التأمين في الجزائر، من خلال الاشارة الى النصوص التنظيمية التي تشرح هذه القواعد، وتتبع نتائج تطبيقها في مدى احترام شركات التأمين الجزائرية لمبدأ كفاية رأس المال، ومدى تطوره هامش الملاءة المالية قبل وبعد الإصلاحات التي شهدها قطاع التأمين و مكونات الالتزامات المقننة والقنوات التوظيفية الموجهة إليها، ومدى احترام شركات التأمين في الجزائر لهذه المؤشرات، قصد ضمان استمراريتها وقدرتها على الوفاء بالتزاماتها، ولقد خلصت نتائج الدراسة الى وجود فائض كبير في هامش الملاءة لشركات التأمين، وفي نفس الوقت ضعف كبير في الايفاء بالالتزامات امام المؤمن لهم والمتمثل في ضعف نسبة التعويض الى هامش الملاءة والتباطؤ في التعويض، مقاسا بالنمو في حجم الاخطار في انتظار التسوية. الكلمات المفتاحية: الملاءة 02، التأمين، هامش الملاءة. تصنيف JEL: G22, Abstract: In this study, we aim to examine the mechanism of applying the three pillars of solvency 02 to the Algerian insurance sector, through the regulatory texts that explain these rules. and follow The results of their application at the Algerian insurance companies, on the respect of the principle of capital adequacy, the extent of its development of the solvency margin before and after the reforms of the Algerian insurance sector, the components of the regulated liabilities, in order to ensure continuity and ability to meet their obligations. The results of the study are: a large surplus in the margin of solvency of insurance companies, while at the same time a significant weakness in the fulfillment of obligations to the insured and the weakness of the proportion of compensation to the margin of solvency , Measured by the growth in the volume of notification pending settlement. Key words: solvency 02, insurance, margin of solvency. Classification jel: G22
Keywords: الملاءة2 ; التامين ; هامش الملاءة